Inducible ablation of dopamine D2 receptors in adult mice impairs locomotion, motor skill learning and leads to severe parkinsonism - Bello Gay, Estefania Pilar (2016)
Motor execution and planning are tightly regulated by dopamine D1 and D2 receptors present in basal ganglia circuits. Although stimulation of D1 receptors is known to enhance motor function, the global effect of D2 receptor (D2R) stimulation or blockade remains highly controversial, with studies showing increasing, decreasing or no changes in motor activity. Moreover, pharmacological and genetic attempts to block or eliminate D2R have led to controversial results that questioned the importance of D2R in motor function. In this study, we generated an inducible Drd2 null-allele mouse strain that circumvented developmental compensations found in constitutive Drd2−/− mice and allowed us to directly evaluate the participation of D2R in spontaneous locomotor activity and motor learning. We have found that loss of D2R during adulthood causes severe motor impairments, including hypolocomotion, deficits in motor coordination, impaired learning of new motor routines and spontaneous catatonia. Moreover, severe motor impairment, resting tremor and abnormal gait and posture, phenotypes reminiscent of Parkinson’s disease, were evident when the mutation was induced in aged mice. Altogether, the conditional Drd2 knockout model studied here revealed the overall fundamental contribution of D2R in motor functions and explains some of the side effects elicited by D2R blockers when used in neurological and psychiatric conditions, including schizophrenia, bipolar disorder, Tourette’s syndrome, dementia, alcohol-induced delusions and obsessive-compulsive disorder.